ISSUES OF STUDYING HUMAN MENTAL STATE IN VARIOUS DISCIPLINES (Journal of Universal Science Research, 2024)
This article examines the multifaceted approach to studying human mental states across various academic disciplines. It explores how psychology, neuroscience, philosophy, sociology, and artificial intelligence each contribute unique perspectives and methodologies to understanding cognitive processes and emotional conditions. The paper highlights the interdisciplinary efforts that are essential for a comprehensive understanding of mental states, discussing key theories, findings, and debates within each field. By synthesizing these diverse viewpoints, the article emphasizes the complexity of mental states and the need for integrated approaches to effectively study and interpret human cognition and behaviour.